Hidrociclones aplicados à separação sólido-líquido de suspensões contendo: areia, esferas ocas de vidro e fluido não newtoniano. - Alves, Daniel (2019)
During oil well drilling, it is essential to control the pressure exerted by the fluid occupying the annular region, formed between the drill string and the sidewall of the well. If the pressure exerted by the fluid is lower than the pore pressure, there will be an undesirable invasion of fluid trapped in the pores into the well. On the other hand, if the pressure exerted by the fluid is very high, the fracture of the rock formation can occur, causing the penetration of the fluid in the rock formation, which in extreme cases can lead to the collapse of the well. The difficulty in controlling the annular pressure when drilling in deep water or ultra-deep water is even greater, since the operating window is usually narrow. In order to adjust the pressure, or weight of the drilling fluid, in the annular region, there is often a need to reduce the density of the fluid. One way to achieve this goal is to inject fine and low density particles into the fluid. Hollow glass spheres is being commonly used. The recovery of these spheres, for later reuse, is fundamental to ensure the economic viability of this method. Mini-hydrocyclones are equipment with great potential for this application because they have high separation efficiency, occupy small space and the capacity limitation can be overcome by installing compact batteries. Hence the purpose of this work is to study the geometric variables: underflow diameter, length of the cylindrical region and angle of the conical region in order to select an geometry for a mini-hydrocyclone (Dc = 30 mm) operating with a pseudoplastic fluid. In the geometry selected, the effects of inlet pressure and sand volumetric concentration on the capacity, liquid ratio, total sand separation efficiency and total spheres separation efficiency were evaluated to determine if spheres were undesirably dragged into the underflow by the sand. The geometry selected showed high efficiency of spheres separation (close to 80%) and sand (94%).Moreover the results demonstrate that for a high sand volumetric concentrations at feed (9%) the sand separation efficiency drops sharply to the order of 68% but high spheres separation efficiencies continue to be achieved, demonstrating that sand is not responsible for a significant drag of spheres to underflow current.